Pendampingan Percepatan Pembuatan Lemang pada UMKM Lemang Banjar: Pengabdian - Rinna Ramadhan Ain Fitriah; Nurfiza Widayati; Selly Swandari; Akbar Lufi Zulfikar; Swadia Gandhi Mahardika; Indra Maulana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Lemang Banjar MSMEs in Samarinda City face various challenges in their production process, such as limited capital, long production process, and unattractive product packaging. This community service program aims to support production acceleration through redesigning packaging design and proposing the use of production aids, especially coconut milk squeezing tools, to improve work efficiency. Activities are carried out through initial surveys, solution discussions, implementation in the field, and monitoring and evaluation. The results show that the new packaging design is able to strengthen product branding and attract consumer interest, while production process efficiency can be improved with more modern equipment solutions. This approach is expected to improve the competitiveness of Lemang Banjar MSMEs in a sustainable manner.